A new species of Myloplus Gill (Characiformes, Serrasalmidae) from the Tumucumaque Mountain Range, Brazil and French Guiana, with comments on M. rubripinnis - Andrade, Marcelo C.; Jégu, Michel; Gama, Cecile S. (Zootaxa, 2018)
A new species of Myloplus Gill is described from Eastern Tumucumaque Mountain Range, drainages of the Oyapock and Araguari rivers between Brazil and French Guiana. The new species is diagnosed by having comparatively large scales on the flanks, resulting in lower counts when compared with congeners, i.e., 59 to 70 total perforated scales on lateral line, 31 to 35 longitudinal scales above lateral line, 24 to 29 longitudinal scales below lateral line, and 22 to 26 circumpeduncular scale rows. The new species most closely resembles Myloplus rubripinnis by sharing with this species a general rounded shape, a similar color pattern, and a high number of rays, i.e., 23 to 25 branched dorsal-fin rays and 35 to 38 branched anal-fin rays in the new species (vs. 24 to 25 and 32 to 40, respectively, in M. rubripinnis). After reviewing the available type-specimens of all Myloplus species, M. rubripinnis is re-diagnosed as having higher counts of branched dorsal-fin rays and anal-fin rays combined to tiny scales on flanks, i.e., 85 to 89 total perforated scales on lateral line, 38 to 45 longitudinal scales above lateral line, 33 to 42 longitudinal scales below lateral line, and 30 to 39 circumpeduncular scale rows.